The effectiveness of cognitive-behavioral play therapy on exam anxiety and academic vitality - Safari, Reza; Heidari, Shaban; Hasanzadeh, Ramazan (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2022)
Background and purpose: Examining the issues and problems of students in the field of education and personality and identifying the factors that probably hinder their personal and social growth is of particular importance in every society. The purpose of this research was to determine the effectiveness of cognitive behavioral game therapy on exam anxiety and academic vitality in elementary school boys. Methods: This research was applied in terms of purpose and in terms of implementation method, it was a semi-experimental type with a pre-test-post-test design with a control group. The statistical population in this research included all male students of primary school in district 2 of Sari city. In this research, a sample consisting of 30 students who were selected by voluntary sampling from among all the male students of primary school in district 2 of Sari city. They were randomly divided into two groups of 15 people (cognitive behavioral play therapy and control group). The data were collected using the children's test anxiety questionnaire (Wren and Benson, 2004) and the academic vitality questionnaire (Martin and Marsh, 2006) and were analyzed by univariate covariance analysis and spss.22 software. The significance level of the tests was considered 0.05. Results: The results showed that cognitive behavioral game therapy led to a significant improvement in the experimental group compared to the control group in reducing exam anxiety (P